2019
DOI: 10.1007/jhep11(2019)004
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic instabilities of generalized exotic BTZ black holes

Abstract: We examine the conjecture that black holes violating the reverse isoperimetric inequality have negative specific heat at constant volume CV [1]. We test this conjecture on the family of generalized exotic Bañados, Teitelbiom and Zanelli (BTZ) black holes and find that CV can be positive even when the reverse isoperimetric inequality is violated, providing a counter example to the conjecture. However in all cases where CV is positive, the specific heat at constant pressure CP is negative, indicating that genera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 29 publications
(33 reference statements)
2
18
0
Order By: Relevance
“…It remains to be shown whether similar doubts could arise also for other Superentropic black holes, for example the recently studied charged BTZ black holes [57][58][59][60] have an apparently similar issue. The charged BTZ black hole is a three dimensional electrically charged solution of the Einstein-Maxwell equations [61]…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…It remains to be shown whether similar doubts could arise also for other Superentropic black holes, for example the recently studied charged BTZ black holes [57][58][59][60] have an apparently similar issue. The charged BTZ black hole is a three dimensional electrically charged solution of the Einstein-Maxwell equations [61]…”
Section: Discussionmentioning
confidence: 94%
“…We therefore suspect that the traditional thermodynamics of this somewhat pathological solution is most likely not the correct one. Finally, in an interesting recent twist, the rotating (uncharged) BTZ black hole, which as a traditional Einstein solution is not superentropic, can be reimagined as a solution of the gravitational Chern-Simons action [58,64]. The thermodynamic parameters become "exotic" (with mass and angular momentum charges reversed and the entropy no longer given by the horizon area).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result consequently leads to a natural conjecture that super-entropic black holes always have C V < 0, making them unstable in the extended thermodynamics. Later, it was found that this conjecture is violated for generalized exotic BTZ black holes in some parameter region [24]. However in this case, the specific heat at constant pressure C P was exhibited to be negative whenever C V > 0.…”
Section: Introductionmentioning
confidence: 99%
“…More relevant discussions can be found in refs. [16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%